Role of design and application on refractory performance - Sarkar, B.; Pal, Prabhat; Saha, P.; Lahiri, P. (2014)
© 2014 The American Ceramic Society.Performance of a refractory lining system primarily depends on design and application. Appropriate selection of the material, anchoring system and provision of adequate thermal expansion are the key elements in a refractory design. This paper highlights select case studies, where performance has been enhanced by small changes in the design. Change of anchor design from fixed to floating type increased refractory life from 6 months to 4 years in CCU cooler. Refractory life increased to almost double by modification of air mixer nozzle in a secondary reformer. Effectiveness of a refractory design largely depends on the application. Some case studies of the refractory failure analysis undertaken by authors are presented in the paper, which reveals wrong application is a major reason of refractory failures in many instances. In oil and gas processing furnaces like crackers, reformers, FCCU, SRU etc, refractory performance becomes vital for smooth operation of these process units. In most cases, licensor's specification adequately defines the essential requirements concerning design but, effective implementation of the same requires review of the detail engineering and application supervision by an independent agency.